2017
DOI: 10.1086/690554
|View full text |Cite
|
Sign up to set email alerts
|

Plasma acylcarnitines are associated with pulmonary hypertension

Abstract: Quantifying metabolic derangements in pulmonary hypertension (PH) by plasma metabolomics could identify biomarkers useful for diagnosis and treatment. The objective of this paper is to test the hypotheses that circulating metabolites are differentially expressed in PH patients compared with controls and among different hemodynamic subtypes of PH associated with left heart disease. We studied patients enrolled in the CATHGEN biorepository with PH (right heart catheterization mPAP ≥ 25 mmHg; n = 280). Of these, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 24 publications
(56 reference statements)
6
23
1
Order By: Relevance
“…By using rats just after 14 days of MCT injection, we found that before significantly increased pulmonary pressure and right ventricle hypertrophy, a complete metabolic reprogramming occurs in the lungs (140). Metabolic profiling indicated that at the early stage in disease development there were significant changes in glycolysis and fatty acids beta-oxidation as well as inflammatory, oxidative stress, and fibrosis biomarkers, which were previously described for developing PH (103, 116, 149, 208). Thus, metabolic reprogramming is an early event that takes place faster than the pathophysiologic changes in the pulmonary vasculature.…”
Section: Metabolic Reprogrammingmentioning
confidence: 62%
See 1 more Smart Citation
“…By using rats just after 14 days of MCT injection, we found that before significantly increased pulmonary pressure and right ventricle hypertrophy, a complete metabolic reprogramming occurs in the lungs (140). Metabolic profiling indicated that at the early stage in disease development there were significant changes in glycolysis and fatty acids beta-oxidation as well as inflammatory, oxidative stress, and fibrosis biomarkers, which were previously described for developing PH (103, 116, 149, 208). Thus, metabolic reprogramming is an early event that takes place faster than the pathophysiologic changes in the pulmonary vasculature.…”
Section: Metabolic Reprogrammingmentioning
confidence: 62%
“…Recently, with the availability of untargeted metabolomic approaches, several reports were published that used metabolic profiling to evaluate possible biomarkers and shifts in metabolites in PAH patients (103, 116, 149, 207–209), animal models of PH (72, 140, 144, 210), and cells (36, 86, 182). The cancer-like proliferation of pulmonary vascular cells requires metabolic adaptation for the heightened demand of dividing cells.…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%
“…These results are notably from patients with severe PAH only and do not depict changes with exercise, a stress which further differentiates the functional capability of PH patients from controls, as exemplified by higher predictive accuracy for PAH and ePH, compared to controls, from our random forest models using paired rest-exercise blood samples. Luo et al 18 also documented higher concentrations of long-chain plasma acylcarnitines in PAH cases versus controls, with different strengths of association based on pre vs. post-capillary PH status, highlighting the need for detailed PH phenotyping. Rhodes et al 19 demonstrated similar metabolic changes and patterns in patients with PAH in addition to metabolic profiles associating with increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, circulating metabolite screens in PH have aimed to identify unique profiles in PH patients and/or distinct PH subtypes for diagnostic and prognostic benefit. Data suggest that certain microRNAs (102,161), plasma acylcarnitines (47,162), glutamate (163), TCA intermediates, amino acids (163,164), transfer RNA-specific modified nucleosides (163), purines, indoleamines, and indoleamine 2,3-dioxygenase-dependent tryptophan metabolites (165) are differentially expressed in plasma among various cohorts of PH patients. Moreover, significant metabolite alterations prognosticated risk of death (163) and correlated with hemodynamic measurements (165).…”
Section: Evolving Translational Technologiesmentioning
confidence: 99%